Nutrients Dynamics in a Tropical Hypersaline Coastal Lagoon (Las Marites, Margarita Island, Venezuela) - López Monroy, F. M.; Troccoli Ghinaglia, L. E.; Poblete, E.; Valerio González, L. (Revista Bio Ciencias, 2017)
The nitrogen and phosphorus enrichment is the main responsible for changes in the trophic status of coastal lagoons. Hence, we have evaluated the distribution of these nutrients, chlorophyll a and variables that directly affect them (temperature, salinity and dissolved oxygen), in the hypersaline coastal lagoon Las Marites, located in Margarita Island, Venezuela. Water samples were collected in the period: April 2005-March 2006 and April 2011-August 2012, at seven stations in the lagoon and an area at the sea, besides having historical records. Traditional spectrophotometric methods were used for the determination of nitrate, nitrite, ammonium and phosphate. Results showed that the spatial distribution of nitrogen and phosphorus in the ecosystem responds to the morphology and bathymetry of the water body. Occurring increases towards the western sector due to point sources (wastewater discharges). The seasonal nutrient cycle is dominated by the sea adjacent coastal upwelling and temporal distribution by anthropogenic action in the vicinity of the lagoon.